Design of a novel hybrid control strategy for multi‐inverter parallel system for resonance suppression - Feng Zheng (Energy Science & Engineering, 2020)
Abstract Comparing with the LCL‐type single‐inverter parallel system, the multi‐inverter parallel system has more complex resonance characteristics which are generated by three type resonance sources (reference current changing in the inverter control system, reciprocal effect among multi‐inverters and grid background harmonic) and cause great negative effects on power system. In order to suppress the resonance problem of LCL‐type multi‐inverters parallel system, a novel control strategy is proposed in this paper based on model current predictive control (MCPC) and two‐degree‐of‐freedom control. Through MCPC, this strategy can reduce the number of current inner‐loop PI of control layer and remove PWM module. Then, a potential robustness can be obtained. From the outer loop of control layer perspective, because MCPC's value function consists of inverter's output current and reference current of control layer inner loop, they can be approximately regarded as equal. And then through constructing the inverse model of control object, the two‐degree‐of‐freedom control can be introduced to realized transfer function unitarization of control layer's outer loop, so that the order difference between numerator's highest order term and denominator's highest order term of inverter resonance transfer function can be reduced. Accordingly, it can be found that with the three type resonance sources, there is no peak value in their resonance transfer functions and their gains all present attenuation effects. Therefore, the resonance problems of multi‐inverter parallel system can be eliminated. Through the theoretical derivation and simulation results, it can be proved that the proposed method can not only enhance the transient performance of multi‐inverter parallel system, but also its resonance problems.